Complexation and Toxicity of Copper in Higher Plants. II. Different Mechanisms for Copper versus Cadmium Detoxification in the Copper-Sensitive Cadmium/Zinc Hyperaccumulator Thlaspi caerulescens (Ganges Ecotype) - Mijovilovich, Ana (American Society of Plant Biologists, 2009)
The cadmium/zinc hyperaccumulator Thlaspi caerulescens is sensitive toward copper (Cu) toxicity, which is a problem for phytoremediation of soils with mixed contamination. Cu levels in T. caerulescens grown with 10 μm Cu(2+) remained in the nonaccumulator range (<50 ppm), and most individuals were as sensitive toward Cu as the related nonaccumulator Thlaspi fendleri. Obviously, hyperaccumulation and metal resistance are highly metal specific. Cu-induced inhibition of photosynthesis followed the “sun reaction” type of damage, with inhibition of the photosystem II reaction center charge separation and the water-splitting complex. A few individuals of T. caerulescens were more Cu resistant. Compared with Cu-sensitive individuals, they recovered faster from inhibition, at least partially by enhanced repair of chlorophyll-protein complexes but not by exclusion, since the content of Cu in their shoots was increased by about 25%. Extended x-ray absorption fine structure (EXAFS) measurements on frozen-hydrated leaf samples revealed that a large proportion of Cu in T. caerulescens is bound by sulfur ligands. This is in contrast to the known binding environment of cadmium and zinc in the same species, which is dominated by oxygen ligands. Clearly, hyperaccumulators detoxify hyperaccumulated metals differently compared with nonaccumulated metals. Furthermore, strong features in the Cu-EXAFS spectra ascribed to metal-metal contributions were found, in particular in the Cu-resistant specimens. Some of these features may be due to Cu binding to metallothioneins, but a larger proportion seems to result from biomineralization, most likely Cu(II) oxalate and Cu(II) oxides. Additional contributions in the EXAFS spectra indicate complexation of Cu(II) by the nonproteogenic amino acid nicotianamine, which has a very high affinity for Cu(II) as further characterized here.